f(x) =
| { |
cx ,
,
c(1 - x) |
0 ≤ x ≤ 1/2
1/2 < x ≤ 1 |

where

0 | . |
p
_{1} p_{2} p_{3}
p_{4} ... |

s _{1}= p_{1} | . |
(p
_{1 }p_{2 }) (p_{1 }p_{3 })
(p_{1 }p_{4 }) ... |

s _{2}= p_{1 }p_{2} | . |
(p
or taking into account that _{1 }p_{2 }p_{1 }p_{3 })
(p_{1 }p_{2 }p_{1 }p_{4 }) ...p
_{k}^{2} = 1 |

. |
(p
_{2 }p_{3 })
(p_{2 }p_{4 }) ... | |

s _{3}= p_{2 }p_{3} | . |
(p
_{3 }p_{4 }) (p_{3 }p_{5 }) ... |

... | ||

s _{n}= p_{n-1 }p_{n} | . |
(p
_{n }p_{n+1 }) (p_{n }p_{n+2 })
... |

Multiplying this formula by

By means of this formula we get

b
_{n} = | { |
b
_{n-1}
1 - b _{n-1} |
if s
_{n} = 0if s
_{n} = 1 |

Now you can repeat all the "chaos story" told for the sawtooth map before. Later it will be repeated for the quadratic map for

Contents Previous: Sawtooth map Next: Strange Cantor repeller